Consciência ambiental: um estudo exploratório sobre sua influência na utilização do gás natural pelos motoristas de táxi do município de São Paulo - Araújo, Bárbara Susana Barbosa de (2015)
The starting point for the construction of this study was the perception that the current societal behavior and business management models do not provide the balance needed for the continuation of environmental resources essential to human survival. The challenges to achieve the widespread sustainable development are immense and, for many, utopian. This research was conducted after admitting that the production of knowledge is one of the guiding pillars of the advancement of the discussions which enable a boost in understanding and engagement within society in favor of a less unsustainable future. This study sought to understand to what extent there is a relationship between the environmental awareness of taxi drivers in São Paulo and the use of natural gas for their vehicles, compared to the survey of the factors that stimulate and discourage the use of this fuel considered less pollutant. The choice of researching on the use of Natural Gas Vehicles (NGV) as an energy source was due to the fact that in Brazil the use of other clean energy sources in the transport sector is extremely incipient. We sought to identify which in practice, are perceived as attributes that encourage and / or inhibit drivers to use NGV. In addition, we sought to understand whether taxi drivers, apart from the technical and economic developments, were also motivated by an environmental concern to collaborate or reinforce the choice of a less polluting fuel than traditional ethanol and gasoline. The results obtained by our descriptive quantitative research, with 73 taxi drivers in São Paulo, preceded by a qualitative exploratory study. Factors related to the financial benefits of the use of CNG were confirmed as the main attractions for using this type of fuel; whereas the necessary investment to adapt the vehicle to the supply of natural gas was appointed as the main to its use. When analyzing the results, it can be concluded that, because there is no evidence that environmental awareness is an important attribute in the decision of taxi drivers to use cleaner fuel, it is necessary to have a greater incentive to use this power source, or any other offering less potential offensive worsening of urban pollution and consequent respiratory diseases, to which the population is subject to. The stimuli may be a result of, among others, tax exemptions, already practiced in some Brazilian municipalities.